Perfil dos pesquisadores com bolsa de produtividade em pesquisa do CNPq da área de saúde coletiva A profile of researchers in public health with productivity grants from the Brazilian National Research Council (CNPq) - Rita Barradas Barata; Moisés Goldbaum (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2003)
O artigo analisa, com base nas informações do currículo Lattes, o perfil dos pesquisadores com bolsa de produtividade em pesquisa do CNPq na área de Saúde Coletiva. A análise levou em conta a formação graduada e pós-graduada, área de atuação, produção e divulgação científica. As comparações são feitas entre as classes de pesquisadores e com dados do diretório de grupos de pesquisa. A maioria dos pesquisadores (70%) são formados em Ciências da Saúde, principalmente em Medicina, ou em Ciências Humanas (18%), principalmente Sociologia. Sessenta por cento fizeram mestrado e doutorado em Saúde Coletiva, mas há entre 20 e 30% de pesquisadores, dependendo da classe, sem formação específica na área. A maioria atua em Epidemiologia. A produção científica, expressa em produtos bibliográficos, varia de 10,56 produtos/ano de obtenção do doutorado para os pesquisadores 2C a 6,60 produtos/ano para os pesquisadores 1A. Para artigos completos publicados em periódicos os valores são 3,56 e 2,87, respectivamente. A produção é divulgada principalmente em periódicos A internacional e, A e B nacional. Os periódicos que concentram a publicação são Cadernos de Saúde Pública e Revista de Saúde Pública. Based on information provided by the Lattes curriculum, this study analyzes the profile of researchers in public health with productivity grants from the Brazilian National Research Council (CNPq). The analysis considered the researcher's undergraduate and graduate degrees, field of expertise, scientific output, and publications. The article discusses comparisons between different categories of researchers and data provided by the CNPq Research Group Directory. Most of the researchers (70%) received their undergraduate degrees either in health sciences, mainly medicine, or the humanities (18%), mainly sociology. 60% have Master's or PhDs in collective health, but some 20 to 30% of researchers, depending on the category, have no specific training in this particular field. Most are currently engaged in epidemiology. Their scientific work, as evidenced by bibliographic output, varies from 10.56 research products per year for level 2C PhD researchers to 6.60 products per year for level 1A researchers. For complete articles published in periodicals, the figures are 3.56 and 2.87, respectively. The output is mainly published in class A international periodicals as well as national periodicals, classes A and B. The periodicals with the greatest concentration of articles are Cadernos de Saúde Pública/Reports in Public Health and Revista de Saúde Pública/Journal of Public Health.